Multimodal Genre of Science Classroom Discourse: Mutual Contextualization Between Genre and Representation Construction - Tang, Kok-Sing; Park, Joonhyeong; Chang, Jina (2021)
This paper argues that meaning-making with multimodal representations in science learning is always contextualized within a genre and, conversely, what constitutes an ongoing genre also depends on a multimodal coordination of speech, gesture, diagrams, symbols, and material objects. In social semiotics, a genre is a culturally evolved way of doing things with language (including non-verbal representations). Genre provides a useful lens to understand how a community’s cultural norms and practices shape the use of language in various human activities. Despite this understanding, researchers have seldom considered the role of scientific genres (e.g., experimental account, information report, explanation) to understand how students in science classrooms make meanings as they use and construct multimodal representations. This study is based on an enactment of a drawing-to-learn approach in a primary school classroom in Australia, with data generated from classroom videos and students’ artifacts. Using multimodal discourse analysis informed by social semiotics, we analyze how the semantic variations in students’ representations correspond to the recurring genres they were enacting. We found a general pattern in the use and creation of representations across different scientific genres that support the theory of a mutual contextualization between genre and representation construction.